A novel medium heavy alloy (MHA) with excellent static/dynamic properties and impact toughness. (15th March 2019) - Li, Y.; Liu, G.Q.; Hu, X.B.; Wu, L.H.; Tan, C.W.; Dravid, Vinayak P.; Liu, S.Z.
Abstract: Conventional tungsten heavy alloys (WHAs) fabricated using powder metallurgic method exhibit a much lower strength than ultrahigh strength steels (UHSSs). Here, we first time designed a novel medium heavy alloy (MHA) of 57Ni-37W-5Co-1Ta fabricated using the casting technology. Compared to WHA, this MHA not only largely reduces the difficulty in manufacturing and post working, but also enhances the toughness by 10 times together with excellent quasi-static and dynamic properties. The superior strength-toughness is attributed to the face-centered cubic (FCC) matrix and/or the nano-sized secondary phases. While the superior dynamic performance is attributed to the widening of adiabatic shear bands (ASBs). Graphical abstract: Unlabelled Image